2017
DOI: 10.5222/ankem.2017.032
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Antibiotic Combination Therapy for Treatment of Colistin Resistant Acinetobacter baumannii: Trimethoprim-Sulfamethoxazole and Colistin Combination

Abstract: ÖZET Acinetobacter baumannii ventilatör ilişkili pnömoni, kan dolaşımı infeksiyonları, cerrahi alan infeksiyonları ve idrar yolu infeksiyonları gibi çeşitli infeksiyonlara yol açan önemli bir nozokomiyal patojen olarak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…It is known that Acinetobacter strains rapidly develop resistance to fluoroquinolone group antibiotics. 24 Yıldız et al 25 , in a study they conducted, looked at the pattern of resistance to fluoroquinolones and showed that this rate was 98.8% to ciprofloxacin and 98.2% to levofloxacin. They interpreted this situation as the development of resistance due to its frequent use as an empirical antibiotic in combination therapy over the years.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Acinetobacter strains rapidly develop resistance to fluoroquinolone group antibiotics. 24 Yıldız et al 25 , in a study they conducted, looked at the pattern of resistance to fluoroquinolones and showed that this rate was 98.8% to ciprofloxacin and 98.2% to levofloxacin. They interpreted this situation as the development of resistance due to its frequent use as an empirical antibiotic in combination therapy over the years.…”
Section: Discussionmentioning
confidence: 99%
“…A.baumannii suşları, florokinolonlar ve aminoglikozitler gibi geniş spektrumlu diğer antibiyotiklere de hızla direnç geliştirmektedirler (21). Yıldız ve ark.…”
Section: Discussionunclassified